Peran konseling dalam mengatasi stres dan kecemasan remaja di era modern - Tamam, Safira Putri (Maliki Interdisciplinary Journal, 2024)
In the modern era, adolescents face various challenges that can trigger stress and anxiety, such as academic pressure, social dynamics, and the influence of social media. Counseling plays a crucial role in helping adolescents cope with these challenges. This article discusses how counseling provides a safe space for self-expression, helps identify triggers of stress and anxiety, and develops effective coping strategies. Additionally, counseling enhances adolescents’ self-esteem and confidence, offers emotional support, and teaches good social and communication skills. By reducing the stigma surrounding mental health issues and providing early intervention, counseling helps prevent stress and anxiety from becoming more serious problems. Through a holistic and supportive approach, counseling significantly contributes to the mental well-being of adolescents, helping them grow into healthy and resilient individuals.